Effect of heat treatment on AlMgGaInSn alloy for hydrogen generation through hydrolysis reaction. (21st September 2017) - Yang, Bobo; Zhu, Jianfeng; Jiang, Tao; Gou, Yongni; Hou, Xiaojiang; Pan, Bowei
Abstract: The composition, microstructure and corrosion behavior of AlMgGaInSn alloy in cast and heat-treatment were investigated by XRD (X-ray diffraction), SEM (scanning electron microscope) and EDS (energy dispersive spectrometer). The hydrogen evolution parameters, and the electrochemical properties based on different heat-treatment parameters conditions and immersion temperature were also tested. As the heat-treated temperature increased, the second phases were found to be spheroidizing or ellipsoidal shape due to the diffusion and solid solution. The reaction can be divided into three stages: i) the amalgamation initial stage; ii) the micro-galvanic reaction for propagation corrosion; iii) the dissolution-precipitation reaction for uniform corrosion. The hydrolysis rate reached the maximum value when the sample was annealed at temperature of 500 °C for 9 h. The hydrogen generation rate and the open electrochemical potential of the activated aluminum under water are both depending on heat treatment time, heat treatment temperature, and reaction temperature. A corrosion mechanism was also proposed in which Mg2 Sn and eutectic phase acted as the induction reaction stage during hydrolysis reaction. Graphical abstract: The left graphic is the corrosion microstructure for the heat treatment aluminum alloy, and the right graphic is the hydrogen evolution curves about samples with different heat treatment temperatures and soaking time under 70 °C when immersed in water. Highlights: A three-stage evolution mechanism between AlMgGaInSn alloys and water is proposed. Raised heat treatment temperature and time on aluminum alloys accompanies with higher hydrogen production. The reaction induction time is controlled by the initial corrosion stage under low temperature.